Application of service oriented software architectures in sports: Team training optimization in cycling - Jaitner, T.; Trapp, M. (International Journal of Computer Science in Sport, 2008)
Advances in Information technologies and microelectronics provide a huge potential for performance monitoring and feedback training in sports. The high dynamics of innovations on one hand as well as constitutional or situational changes of constellations and objectives in many sports disciplines on the other support the notion of more flexible and adaptive systems. In this paper a software approach based on a service oriented architecture is presented that supports dynamic integration of heterogeneous devices in a sports-specific environment. A first application has been established to improve team training in cycling. The objective of the team cycling training system (TCTS) is to improve the training of a whole group of cyclists in a way that each cyclist should meet his predefined exercise intensity as close as possible.